A creeper camps out - Mann, Greyson (Mann, Greyson. Creeper diaries, 2019)
When Gerald is forced to spend a night in the woods during summer camp, he finds an abandoned woodland mansion to camp out in, but first must stand up to the rival villagers who have claimed the mansion.